Faktor – Faktor yang Mempengaruhi Manajemen Laba pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Winarti, Aulia; Ramashar, Wira; Aristi, Mentari Dwi (Economics, Business and Management Science Journal, 2025)
This study aims to determine the effect of information asymmetry, free cash flow, earning power, and bonus plans on profit management in Transportation and Logistics companies listed on the Indonesia Stock Exchange in 2021-2023. This study uses a data collection method in the form of financial reports obtained through www.idx.co.id. The population in this study were all companies listed on the Indonesia Stock Exchange, totaling 943 companies. The sampling technique in this study used the purposive sampling method with a sample size that met the criteria of 15 companies in 3 years of observation so that a sample size of 45 data was obtained. This study uses multiple linear regression analysis with the help of SPSS 25. The results of the study indicate that information asymmetry, free cash flow, and earning power have an effect on earnings management in Transportation and Logistics companies listed on the Indonesia Stock Exchange. The bonus plan does not affect earnings management in Transportation and Logistics companies listed on the Indonesia Stock Exchange.